2010
DOI: 10.1094/pdis-94-4-0487c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fruit Basal Rot by Ceratocystis paradoxa on Coconut in Taiwan

Abstract: Since 2005, coconut fruits (Cocos nucifera L.) harvested from trees in southern Taiwan have shown symptoms of a fruit rot disease. The disease occurs only on harvested coconut fruits and is more serious during warmer seasons. Principal symptoms are blackening of the exocarps, mesocarps, and then the endocarps of coconut fruits from pedicel end or wounds on fruits. A fungus was consistently recovered from diseased fruits. Colonies on potato dextrose agar (PDA) were white, becoming black 1 to 2 days later, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…At 15°C temperature, the mycelial growth was inhibited extremely, maximum mycelia growth was recorded at 35°C. Present results are in conformity with the findings of Tzeng and Sun (2010), which cited that the optimum temperature for hyphal growth of Thielaviopsis paradoxa was found at 25 to 30°C.This fungus did not grow at temperatures lower than 10°C or higher than 35°C. Yadahalli et al (2007) reported the maximum vegetative growth of Thielaviopsis paradoxa, causing sett rot of sugarcane, at temperature of 25-30°C.…”
Section: Resultssupporting
confidence: 93%
“…At 15°C temperature, the mycelial growth was inhibited extremely, maximum mycelia growth was recorded at 35°C. Present results are in conformity with the findings of Tzeng and Sun (2010), which cited that the optimum temperature for hyphal growth of Thielaviopsis paradoxa was found at 25 to 30°C.This fungus did not grow at temperatures lower than 10°C or higher than 35°C. Yadahalli et al (2007) reported the maximum vegetative growth of Thielaviopsis paradoxa, causing sett rot of sugarcane, at temperature of 25-30°C.…”
Section: Resultssupporting
confidence: 93%
“…This species was also reported causing post-harvest diseases in banana, carambola, guava and pineapple (Reyes et al, 1998;Junqueira et al, 2001;Ploetz, 2003). This pathogen causes stem bleeding (Warwick & Passos, 2009;Freire & Martins, 2010) and fruit basal rot of the coconut at field conditions (Rossetti, 1955;Camargo & GimenesFernandes, 1997;Tzeng & Sun, 2009;Tzeng et al, 2010) and external post-harvest disease on coconut (Tzeng & Sun, 2009;Tzeng et al, 2010). Thus, this is the first report of postharvest internal rot disease on immature coconut caused by C. paradoxa.…”
mentioning
confidence: 92%